Factors Impacting Teachers' Happiness on Higher Education in Zhanjiang University of Science and Technology, China - Xie, Qinghua (Scholar: Human Sciences, 2025)
Purpose: The study explores the correlation between factors such as teachers' income, teachers' wealth, teachers' health, sense of gain, sense of fairness, and teachers' happiness. By strengthening the influencing factors, an appropriate strategic plan is identified to enhance teachers' happiness level ultimately. Research design, data, and methodology: The study employed the Instrument of Organization Culture (IOC) as a measure of validity and Cronbach's alpha (n=30) as a measure of reliability. Multiple linear regression (MLR) analysis was conducted on the valid questionnaires of 228 teachers from Zhanjiang University of Science and Technology to validate the significant relationships between variables. Subsequently, a strategic plan was implemented for 16 weeks involving a selected group of 30 teachers. Quantitative pre- and post-strategic plan stage results were compared using paired-sample t-tests. Results: In the multiple linear regression study, we found that teachers' income, teachers' wealth, teachers' health, sense of gain, and sense of fairness have a significant impact on teachers' happiness. The results of the paired-sample t-test indicate that all variables between the pre-and post-strategic plan stages show significant differences. Conclusions: Teachers' income, teachers' wealth, teachers' health, sense of gain, and sense of fairness can enhance the happiness of teachers at Zhanjiang University of Science and Technology.